Penerapan Micro Frontend dengan Next.js dan Module Federation pada Aplikasi Cash Management - Fikri, Muhammad; Drehem, Ishom Muhammad; Adriansyah, Ahmad Rio (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The digitalization of banking has made cash management applications essential for business efficiency; however, the monolithic architecture of the front-end in PT. Bank XYZ's cash management application presents significant challenges in terms of scalability and flexibility, particularly with the cash pooling feature. This study implements a Micro Frontend architecture using Next.js and Module Federation to enhance development and maintenance efficiency. The results show that build times have been reduced from 1 hour to 37 minutes, with an average build time of 12 minutes achieved through parallel processes. Deployments have also become faster, with only a few hours between releases. A survey of 11 respondents, including developers, quality assurance personnel, and other key stakeholders, recorded an average satisfaction score of 4.44 out of 5, indicating strong support. This implementation accelerates feedback loops, facilitates parallel development, and streamlines the feature release process, making it highly applicable to all features within the cash management application, thereby improving scalability and flexibility comprehensively.